KONTRIBUSI INDUSTRI KECIL DALAM PENINGKATAN KESEJAHTERAAN MASYARAKAT: (STUDI KASUS PADA PENGRAJIN TOPI PURUN DI DESA SUKA MAKMUR KECAMATAN BINJAI KABUPATEN LANGKAT) - Aswin Fahmi; Aminullah Marlis Tanjung; M. Radiansyah; M. Guffar Harahap (CV. Barokah Publsiher, 2023)
This research was prepared with the aim of knowing the efforts to maintain a small industrial business carried out by purun hat craftsmen in Suka Makmur Village, Binjai District, Langkat Regency, and the contribution of small industry of purun hats for improving the welfare of purun hat craftsmen in Suka Makmur Village, Binjai District, Langkat Regency. The method used is qualitative with the main informants of the Village Head and Pengarin Topi Purun through interview instruments. Data analysis used qualitative techniques of interactive models. Based on the results of the research conducted, it can be concluded that youpaya maintain the small industrial business carried out by purun hat craftsmen in Suka Makmur Village, District Binjai Langkat Regency is carried out through support efforts from the Village Government and also the development of expertise from purun hat craftsmen to other communities through sharing experience and sharing skills with the community so that more and more are able to do business making purun hats. Furthermore, the contribution of the small industry of purun hats for improving the welfare of purun hat craftsmen in Suka Makmur Village, Binjai District, Langkat Regency is very realistic and real because of the efforts made by craftsmen able to meet the needs of family life both primary, secondary, and tertiary in nature. Then viewed from the aspect of economic science through income analysis and business efficiency, it turns out that the industry has advantages and is efficient to maintain and continued because it has an efficiency value greater than the number one, namely 1.27 > 1